ХУДОЖНІЙ ОБРАЗ ПЕРПЕТУУМ МОБІЛЕ В СОНАТІ ДЛЯ ВІОЛОНЧЕЛІ ТА ФОРТЕПІАНО Б. БРІТТЕНА - Борисенко Tетяна Вікторівна (International Journal of Innovative Technologies in Social Science, 2019)
Perpetuum mobile is a multi-valued cultural phenomenon, it symbolizes continuous movement. In contrast to the mechanistic movement aimed at overcoming space, the perpetuum mobile coincides with the concept of movement in philosophy. Even the ancient philosophers knew that the world is constantly moving, changing (Heraclitus). Modern scientists, in particular J. Deleuze, interpret movement as “events” that reflect the interaction of bodies, but are not bodies themselves. In culture, the perpetuum mobile is understood as an image created by certain means of expressiveness in different types of art and has a generalizing character. Among its signs are symbolism, incompleteness or repeatability, non-orientation, cyclicity. The perpetuum mobile is embodied as a sound image in musical works (or its parts) and is manifested at the syntactic and compositional levels of organization of musical material. The article describes the features of the embodiment of the perpetuum mobile in Sonata for cello and piano by Benjamin Britten.